UPAYA PENYELESAIAN KONFLIK PERTANAHAN DI DESA PARINDING KABUPATEN ENREKANG PERSPEKTIF SIYASAH SYAR’IYYAH - Oktapiana, Adelia; Hasan, Hamzah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
This study aims to find out how the background of land conflicts and the authority of the Head of Parinding Village, Enrekang Regency, in resolving these conflicts and how siyasah syar'iyyah views land conflicts and their resolution mechanisms. The research method used is field research with syar'i, juridical, and sociological approaches, data sources in the form of primary data and secondary data. The results showed that one of the causes of land conflicts was the absence of evidence of ownership of land controlled by the citizens of the community and based only on oral messages from each heir. The mechanism for resolving conflicts that occur can be carried out through mediation by the village head as a mediator and the results are stated in the minutes signed by the conflicting party. The conflict resolution mechanism carried out by the village head is in accordance with the principles of conflict resolution in Islam, known as Ash shulhu, which is the resolution of conflicts by peaceful means through deliberation.